Development of A Material Efficiency Assessment Tool for Metal Stamping Product - Ruslan, Muhd Fauzan Hakim; Ho Fu Haw (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Implementing material efficiency in manufacturing results directly in cost and energy savings in transformation, transportation, and disposal, along with reduced greenhouse gas emissions. The purpose of this study is to develop an assessment tool to evaluate material efficiency performance for metal stamping product from the aspect of machine factors, material factors and product factors. Analytic Hierarchy Process (AHP) approach was chosen for data collection and data analysis to obtain the importance weightage of criteria before being used to develop the assessment tool. The result show that in metal stamping process, product shape and material size give more influences, whereas by-product and machine capacity are giving least influence to material efficiency performance. The assessment tool was validated by experts to get the validation and feedback on the assessment tool developed for improvement. The development of the assessment tool perhaps could help the industry practitioners to determine their product design in term of material efficiency performance in metal stamping process.